Global system segregation enhances reserve in normal aging and Alzheimer's disease: Reserve and resilience: Opportunities and mechanisms for dementia prevention. (7th December 2020) - Ewers, Michael; Frontzkowski, Lukas; Neitzel, Julia; Rubinski, Anna; Habeck, Christian; Gordon, Brian A; Benzinger, Tammie LS; Levin, Johannes; Cruchaga, Carlos; Goate, Alison M; Fagan, Anne M; Karch, Celeste M; et al.
Abstract: Background: Epidemiological studies suggest that reserve capacity is associated with a significant delay of cognitive decline by up to 4 years in aging and dementia. Identifying brain substrates of reserve is a pivotal step to define potential intervention targets for brain stimulation in order to enhance reserve. We previously showed that higher global connectivity of specific richly connected hub regions contribute to reserve (Franzmeier et al. Brain 2018, Neitzel et al. Neurology 2019). However, apart from the role of local hubs, functional mechanisms at the level of major functional networks that support reserve are poorly understood. The segregation of the brain's major functional network is a fundamental brain property that supports higher cognitive function (Chan et al. PNAS 2014, 2018). We hypothesized that higher system segregation is associated with attenuated cognitive decline in normal aging and Alzheimer's disease (AD). Method: We included 255 cognitively normal elderly subjects (age=52.48±16.12) from the RANN study, 108 individuals with autosomal‐dominant AD and their sibling non‐mutation carriers (n=71) from DIAN, and 152 amyloid‐positive subjects across the clinical AD‐spectrum from ADNI. Based on resting‐state fMRI‐assessed 400‐ROI functional connectivity matrix, we computed system segregation as the difference of within‐network and between‐network connectivity normalized to the within‐network connectivity. Higher segregation scores indicate higher segregation between the networks. In linear regression analyses, we tested whether higher system segregation was associated with 1) higher cognitive performance in elderly subjects, and 2) for AD, attenuated cognitive decline at a given level of disease severity (as measured by "estimated years from dementia symptom onset" (EYO) in autosomal‐dominant AD, and by 18F‐AV1451 tau‐PET in early‐Braak‐stage ROIs in sporadic AD). Result: In cognitively normal subjects, higher system segregation was associated with higher composite scores of global cognition (p=0.001, Figure 1). For AD, higher system segregation was associated with an attenuated effect of disease severity on global cognition in autosomal‐dominant AD (interaction EYO by system segregation: p = 0.007, Figure 2), and an attenuated association between tau‐PET and ADAScog in sporadic AD (p=0.0009, Figure 3). Conclusion: System segregation is associated with higher cognitive abilities in aging and enhances reserve capacity in Alzheimer's disease.